LncRNA-mediated regulation of cisplatin response in breast cancer - Azizidoost, Shirin; Sheykhi-Sabzehpoush, Mohadeseh; Dari, Mahrokh Abouali Gale; Józkowiak, Małgorzata; Niebora, Julia; Domagała, Dominika; Data, Krzysztof; Dzięgiel, Piotr; Mozdziak, Paul; Farzaneh, Maryam; Kempisty, Bartosz (Pathology, research and practice, 2024)
Breast cancer is a prevalent and aggressive disease characterized by high metastasis, recurrence, and mortality rates. While cisplatin is an effective chemotherapy drug, its use is limited by its toxic effects on the body. Despite advancements in therapeutic strategies, the therapeutic response is often unsatisfactory due to drug resistance, leading to poor prognosis. Recent studies have shown that cisplatin interacts with long non-coding RNAs (lncRNAs) and accelerates the development of resistance in tumor cells to therapy. This interaction highlights the complex mechanisms involved in the response of cancer cells to chemotherapy. Several lncRNAs have been identified as key players in mediating cisplatin resistance in breast cancer. These lncRNAs include SNHG15, HULC, HCP5, MT1JP, LncMat2B, DLX6-ASL, Linc00665, CARMN, and Lnc-EinRP44-3:6. These lncRNAs have been shown to target microRNAs and mRNAs and modulate the expression of genes involved in cisplatin resistance, which is important in treating breast cancer.
Keywords: Breast Neoplasms; Long non-coding RNAs; lidé; regulace genové exprese u nádorů; Cisplatin; cisplatina; Antineoplastic Agents; Breast cancer; chemorezistence; ženské pohlaví; protinádorové látky; Humans; Gene Expression Regulation, Neoplastic; nádory prsu; RNA dlouhá nekódující; Resistance; Female; RNA, Long Noncoding; Drug Resistance, Neoplasm